Neoglyphs of Alexander Sommer Batek - Hanzelinova L., Zapiyeva M. (Human and Society, 2018)
among all attempts to create a planned language, one cannot but pay attention to Alexander Sommer Batek's pasigraphic system. The name of this system «neoglyph» comes from the term «hieroglyphs», which indicates the similarity of both sign systems. The essence of the concept is to describe the whole concept in one picture. In order to record a speech, it is necessary to add those concepts to a logical chain, supplementing the drawings with necessary grammatical signs. Neoglyphs can be deciphered by carriers of different languages. However, together with its author, its eubiotics, Esperanto and the idea of universal understanding neoglyphs were gradually ousted from the public's consciousness in 1944. Meanwhile, we still can find interesting and inspiring ideas in the works of Alexander Sommer Batek.
Keywords: взаимопонимание; literary language; международный плановый язык; художественный язык; пазиграфическая система; неоглифы; Александер Соммер Батек; artificial international language; pasigraphic system; neoglyphs; Alexander Sommer Batek; mutual understanding